Systemic Representation of Sophisticated Economic Structures of Oil and Gas Sector of the Economy - Deberdieva, Elena M. (International Journal of Economics and Financial Issues, 2016)
Complex economic agents are always a subject of scientific research aimed at systemizing and generalizing the existing knowledge and finding out new knowledge about their structure, general and peculiar properties, and transformational change. With regard to this, one of the widely used definitions here is the "sophisticated economic structure" (SES), the conceptual aspect of which is not represented in scientific literature. In this paper, the author describes the content of the said definition based on the general scientific methods of systemic and logical analysis, analogies and generalization. Its key properties are outlined as follows: emergence, hierarchy, purposefulness. As a result of the study, the oil and gas economic agents’ belonging to sophisticated economic structures has been proven. The key attributes that allow ranking the oil and gas companies as sophisticated are the multi-element composition, managerial and production complexity, a large quantity of internal relationships and interaction with the external environment. As a result of the research, a system model has been developed that describes the objectives being set, internal and external environment parametrically, and variants are outlined of systemic and structural representation of oil and gas companies reflecting the levels of managerial hierarchy, composition of adjustable elements of the value-added chain in the oil and gas sector of the economy. Keywords: Sophisticated economic structure; system properties; oil and gas company; system approach; integrated structure; managerial hierarchy. JEL Classifications: F15; L95